2018
DOI: 10.1007/s10903-018-0707-8
|View full text |Cite
|
Sign up to set email alerts
|

Important Gaps in HIV Knowledge, Attitudes and Practices Among Young Asylum Seekers in Comparison to the General Population

Abstract: Migrants are disproportionately affected by HIV in many European countries, including Finland. We aimed to compare the HIV-related knowledge, attitudes and practices (KAP) of young asylum seekers to those of the general young adult population. Two cross-sectional surveys were conducted among 20- to 25-year-old young adults: The TIE study among asylum seekers (n = 47) and the World AIDS Day 2014 study among the general population (n = 485). Important gaps in HIV KAP were identified especially among the young as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The more people are educated about the virus and its route of transmission, the less they would engage in risky behaviors and the less judgmental they act towards PLWHA [18]. Moreover, the younger generation represents the next generation on which HIV prevention should be most focused on; thus investment should target this generation to promote safe sexual practices [19].…”
Section: Plos Onementioning
confidence: 99%
“…The more people are educated about the virus and its route of transmission, the less they would engage in risky behaviors and the less judgmental they act towards PLWHA [18]. Moreover, the younger generation represents the next generation on which HIV prevention should be most focused on; thus investment should target this generation to promote safe sexual practices [19].…”
Section: Plos Onementioning
confidence: 99%
“…Interestingly, in our sample population the acceptance of HIV/HCV screening was greater in migrants who had higher levels of education and had spent longer times away from their homelands; this data must be considered in the counseling strategy to simplify intervention and make it effective in the majority of the people ( Tiittala et al, 2018 ).…”
mentioning
confidence: 84%
“…It is estimated that 91% of people living with HIV know their status, that 76% of people with HIV are on ART, and that 67% have a suppressed viral load, indicating that Finland has not yet achieved the UNAIDS target of 90-90-90 (UNAIDS, 2018). It has also been suggested that immigration from high HIV prevalence countries has contributed to the HIV epidemic in recent years, particularly as levels of HIV knowledge appear to be poorer in migrant populations compared to the general population (Tiittala et al, 2018). HIV care in Finland is free of charge, and patients can initiate ART upon diagnosis.…”
Section: Hiv In Finland: An Epidemiological Snapshotmentioning
confidence: 99%